(untitled) (Revista INTEREDU11, 2021)
The main objective of this article was to find the relationship between the existential needs of the cognoscent subject and the ontological principles of knowledge, from which the arguments on the purposes of education are built, from the perspective of humanist psychology, assuming these are due to certain cognoscent subject’s existential needs which are directly related to certain ontological principles of knowledge, depending on circumstances of mode, time and place. From the analysis carried out it is revealed the existence of a relationship of dependence or correspondence between the existential needs of the cognoscent subject and the ontological principles of knowledge, from which the purposes of education in humanist psychology are built. Amongst the conclusions, it is observed that the humanist-psychology theory applied to education neglects the sociocultural, psychogenetic, cognitive, psychoanalyst and behavioral aspects of education, which were discussed in depth by Vygotsky, Piaget, Ausubel, Freud and Skinner, as well as by their followers.